Analysis of students career interests of senior high school based on Holland's career interest theory - Sembiring, Mimpin; Tarigan, Thomas Natalisa; Lumbbanbatu, Johannes Sohirimon (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aims to investigate and explore students' career interest tendencies based on Holland's career interest theory, which categorizes career interests into 6 types, RIASEC (Realistic, Investigative, Artistic, Social, Enterprising, and Conventional). The subjects of this study were XII grade students at RK Serdang Murni Lubuk Pakam High School, Deli Serdang Regency, North Sumatra as many as 121 students. This research methodology uses a quantitative approach using a modified Holland career interest test instrument, which consists of 54 question items. Data analysis resulted in a comprehensive mapping of the participants' career preferences, with an average overall career interest score of 2.87, which was categorized as Moderate. The findings revealed that students tended to be more interested in careers related to Social and Enterprising aspects, with lower interest in Realistic and Investigative careers. The implications of this study are expected to make a significant contribution in helping schools to design more targeted interventions in fostering and guiding students' career aspirations more effectively.